Some Progress on Interferometry Techniques Applied to Particle Measurements. (2015) - Gréhan, Gérard; Brunel, Marc; Coetmellec, Sébastien; Garo, Annie; Lebrun, Denis; Meunier-Guttin-Cluzel, Siegfried; Saengkaew, Sawitree; Wu, Yingchun; Wu, Xue Cheng; Chen, Ling Hong
Abstract: The aim of this paper is to present some new developments in particle characterization. More precisely, the paper will be focused on the description of some progresses in the characterization of particles by interferometric methods which are generally considered as the most accurate ones. Three standard configurations will be presented and discussed: i) Interference between scattered light from a particle and a single reference beam (holography), ii) Interference between different kinds of light scattered by a single particle (ILIDS), iii) Interference between the light scattered from different particles. A special attention will be devoted to the possibility to obtain 3D information on the particle location.